How Do Users Interact with AI Features in the Workplace? Understanding the AI Feature User Journey in Enterprise - Hanses, Sarah; Wang, Jennifer (CHI 2022, 2022)
This paper investigates the use of AI features - intelligent attributes in products - in the workplace with enterprise users who engage with AI enabled systems through a variety of touchpoints. Oftentimes, product teams developing AI features face a siloed view of AI experiences, and this work aims to present an end-to-end understanding of the range of enterprise users and their experiences when interacting with AI in the workplace. The purpose is to identify the phases in the AI feature journey for enterprise users across their spectrum of experiences, perceptions, and technical acumen. This paper presents this journey of enterprise users working with AI features, analyzes existing challenges and opportunities within this journey, and proposes recommendations to address these areas when planning, designing, and developing AI features for business applications.